A randomised control trial of short term efficacy of in-shoe foot orthoses compared with a wait and see policy for anterior knee pain and the role of foot mobility. Issue 4 (18th September 2011) - Mills, Kathryn; Blanch, Peter; Dev, Priya; Martin, Michael; Vicenzino, Bill
Abstract : Objectives: To investigate the short-term clinical efficacy of in-shoe foot orthoses over a wait-and-see policy in the treatment of anterior knee pain (AKP) and evaluate the ability of foot posture measures to predict outcome. Design: Single-blind, randomised control trial. Participants: Forty participants (18–40 years) with clinically diagnosed AKP of greater than 6-week duration, who had not been treated with orthoses in the previous 5 years. Intervention: Prefabricated orthoses perceived as most comfortable from a selection of 3 different hardness values compared with a wait-and-see control group. Outcome measures: Participant-perceived global improvement, Kujala Patellofemoral Score, usual and worst pain severity over the previous week and the Patient Specific Functional Scale measures at 6 weeks. Results: Foot orthoses produced a significant global improvement compared with the control group (p = 0.008, relative risk reduction = 8.47%, numbers needed to treat = 2). Significant differences also occurred in measures of function (standardised mean difference = 0.71). Within the intervention group, individuals who exhibited a change in midfoot width from weight bearing to non-weight bearing of >11.25 mm were more likely to report a successful outcome (correct classification 77.8%). Conclusion: This is the first study to show orthoses provide greater improvements in AKP than a wait-and-see approach. Individuals with greater midfoot mobility are more likely to experience success from treatment. Trial Registration: ACTRN12611000492954